Colloidal interfaces in confinement - Jamie, E (2011)
A fluid-fluid demixing colloid-polymer system provides us with an opportunity to study interfacial phenomena that cannot be observed in molecular systems due to unfavourable length and timescales. We develop such a system compatible with cells of varying dimensions, allowing us to investigate confined interfacial behaviour in real space using Confocal Scanning Laser Microscopy. The degree to which a system is affected by the sedimentation-diffusion gradient is dependent on the ratio of the suspension height to the gravitational length of the colloids. We illustrate that we may control the distance of our interface to the critical point by altering the suspension height, determining the importance of the gravitational field. Furthermore, the timescale on which the sedimentation- diffusion gradient is established is considerably longer than that of initial fluid-fluid demixing. We show that after the formation of the macroscopic interface, the system passes through a series of local mechanical equilibria on the way to achieving full equilibrium. Should the system be of sufficient height, it will pass through the gas-liquid critical point opening up new ways to study critical phenomena. The time and length scales of the fluid-fluid demixing of our system may be manipulated by altering the density and viscosity of our solvent. We exploit a slowed phase separation process to study the interplay between demixing and wetting phenomena of systems in the vicinity of a single wetting surface, and confined between two parallel plates. We demonstrate that the presence of a surface strongly affects the morphology of phase separation. The growth of the wetting layer is determined by the demixing regime of the system, and may be accelerated by hydrodynamics. The additional restriction by a second surface limits the lengthscale of coarsening domains and may further alter the mechanism of wetting layer growth.